Stepping down the dose of inhaled corticosteroids for adults with asthma - Crossingham, Iain (Cochrane Database Syst Rev, 2017)
BACKGROUND: Asthma is a condition of the airways affecting more than 300 million adults and children worldwide. National and international guidelines recommend titrating up the dose of inhaled corticosteroids (ICS) to gain symptom control at the lowest possible dose because long‐term use of higher doses of ICS carries a risk of systemic adverse events. For patients whose asthma symptoms are controlled on moderate or higher doses of ICS, it may be possible to reduce the dose of ICS without compromising symptom control. OBJECTIVES: To evaluate the evidence for stepping down ICS treatment in adults with well‐controlled asthma who are already receiving a moderate or high dose of ICS. SEARCH METHODS: We identified trials from the Specialised Register of the Cochrane Airways Group and conducted a search of ClinicalTrials.gov (www.ClinicalTrials.gov) and the World Health Organization (WHO) trials portal (www.who.int/ictrp/en/). We searched all databases from their inception with no restriction on language. We also searched the reference lists of included studies and relevant reviews. We performed the most recent search in July 2016. SELECTION CRITERIA: We included randomised controlled trials (RCTs) of at least 12 weeks' duration and excluded cross‐over trials. We looked for studies of adults (aged ≥ 18 years) whose asthma had been well controlled for a minimum of three months on at least a moderate dose of ICS. We excluded studies that enrolled participants with any other respiratory comorbidity. We included trials comparing a reduction in the dose of ICS versus no change in the dose of ICS in people with well‐controlled asthma who a) were not taking a concomitant long‐acting beta agonist (LABA; comparison 1), and b) were taking a concomitant LABA (comparison 2). DATA COLLECTION AND ANALYSIS: Two review authors independently screened the search results for included studies, extracted data on prespecified outcomes of interest and assessed the risk of bias of included studies; we resolved disagreements by discussion with a third review author. We analysed dichotomous data as odds ratios (ORs) using study participants as the unit of analysis and analysed continuous data as mean differences (MDs). We used a random‐effects model. We rated all outcomes using the GRADE (Grades of Recommendation, Assessment, Development and Evaluation) system and presented results in 'Summary of findings’ tables. MAIN RESULTS: We included six studies, which randomised a total of 1654 participants (ICS dose reduction, no concomitant LABA (comparison 1): n = 892 participants, three RCTs; ICS dose reduction, concomitant LABA (comparison 2): n = 762 participants, three RCTs). All included studies were RCTs with a parallel design that compared a fixed dose of ICS versus a 50% to 60% reduction in the dose of ICS in adult participants with well‐controlled asthma. The duration of the treatment period ranged from 12 to 52 weeks (mean duration 21 weeks; median duration 14 weeks). Two studies were performed in the setting of primary care, two were performed in the secondary care setting and two reported no information on setting. Meta‐analysis was hampered by the small number of studies contributing to each comparison, combined with heterogeneity among outcomes reported in the included studies. We found the quality of synthesised evidence to be low or very low for most outcomes considered because of a risk of bias (principally, selective reporting), imprecision and indirectness. Although we found no statistically significant or clinically relevant differences between groups with respect to any of the primary or secondary outcomes considered in this review, the data were insufficient to rule out benefit or harm. AUTHORS' CONCLUSIONS: The strength of the evidence is not sufficient to determine whether stepping down the dose of ICS is of net benefit (in terms of fewer adverse effects) or harm (in terms of reduced effectiveness of treatment) for adult patients with well‐controlled asthma. A small number of relevant studies and varied outcome measures limited the number of meta‐analyses that we could perform. Additional well‐designed RCTs of longer duration are needed to inform clinical practice regarding use of a 'stepping down ICS' strategy for patients with well‐controlled asthma.